Situation and Problem of Access to Public Health Service of Migrant Workers in Songkhla Province - จารุพันธ์, สุดี; ทัศศรี, จีรเนาว์ (Disease Control Journal, 2009)
This study aimed to explore viewpoints, beliefs and practices about health, health care service, problem and recommendation toward health care services among foreign labors in Sadao District, Songkhla Province. The data were collected through interviewing form and questionnaire during January to April 2007. The obtained data were analyzed using descriptive statistics: frequency and percentage. The results found that most of our subjects have correct viewpoints or beliefs toward physical health care: (1) having multi-partners may cause to HIV infection and other sexually transmitted diseases (93.02%), (2) performing annual health checking is a manner to improve health care (92.36%), and (3) exercise is good for health (92.09%). Whereas, they had incorrect beliefs on two items: using condom during having sexual intercourse reduced sexual satisfaction (72.46%) and sterilization caused unhealthy (69.43%). About their practices toward routine/daily health, the study revealed that (1) washing hands every time before having meals (36.94%), (2) drinking fresh and clean water 6-8 glasses per day (28.10%) and (3) washing mouth and brushing teeth every time after meals (27.31%). Forty percents of them had problems for caring themselves because of late-night working (40.92%), hard working (27.72%) and uncertainty of working time (21.78%). The problems for accessing to health care services were that they had not sufficient knowledge about the steps of getting services (60.05%) and unclear communication with health care providers (46.50%). Their recommendations for improving health care services among foreign labor were having translator (64.43). This study’s results might be useful for improving health care service system among foreign labors which was appropriate for both clients and providers, for example, determining activities and contents for providing the correct health promotion and prevention, coordinating with their employers and reducing steps of services that appropriate for accessing to services, including public relation for accessing to governmental health care facilities and building networks or volunteers in health care among foreign labors.